Geiger counter in use at U.S. Department of Agriculture facility (1950)
View of chemist William A. Jackson using a Gieger counter to examine a package at an unidentified U.S. Department of Agriculture facility. The U.S.D.A. commonly used radioactive material for a variety of research and testing, including the study of radioactive substances as fertilizer, as well as to model the impacts of radioactive material in soil and test the effectiveness of new insect control techniques or materials.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Chemists; Geiger-Müller counters; Fertilizer industry--Equipment and supplies; United States. Department of Agriculture; Employees